2013
DOI: 10.1161/circulationaha.113.002654
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D in Atherosclerosis

Abstract: A therosclerosis, the principal cause of cardiovascular diseases (CVDs), is a process that involves a complex interplay among different factors and cell types, including cells of the immune system (T cells, B cells, natural killer cells, monocytes/macrophages, dendritic cells) and cells of the vessel wall (endothelial cells [ECs], vascular smooth muscle cells [VSMCs]). The atherogenic process evolves in different stages, starting from inflammatory endothelial activation/ dysfunction and resulting in plaque vul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
172
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(226 citation statements)
references
References 144 publications
6
172
1
10
Order By: Relevance
“…Kassi et al [44] suggested that a principal contributory factor to endothelial dysfunction is the diminished availability of NO, and the rise in the production of free radicals. Hence, the proposed direct mechanism by which vitamin D may improve endothelial function may be by enhancing nitric oxide production and decreasing the production of free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Kassi et al [44] suggested that a principal contributory factor to endothelial dysfunction is the diminished availability of NO, and the rise in the production of free radicals. Hence, the proposed direct mechanism by which vitamin D may improve endothelial function may be by enhancing nitric oxide production and decreasing the production of free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Estos resultados contrastan con estudios que han mostrado que los valores bajos de VD se asocian a un estado inflamatorio sistĂ©mico, favorecen la resistencia a la insulina y activan el sistema renina-angiotensina-aldosterona, con la subsecuente elevaciĂłn de la presiĂłn arterial y la hipertrofia del mĂșsculo cardiaco y de las cĂ©lulas musculares lisas [28][29][30] . En concordancia con estos hallazgos, varios estudios observacionales han reportado una asociaciĂłn entre la deficiencia de 25(OH)D y la presencia de EAC clĂ­nica 13,31-33 y subclĂ­nica [34][35][36][37][38] .…”
Section: Discussionunclassified
“…processes characteristic for atherosclerosis, including vascular cell growth, migration, and differentiation, immune response modulation, cytokine expression, and inflammatory and fibrotic pathways [762] . Vitamin D deficiency is affecting more than one billion people to approximately 50% of population worldwide [762][763][764] .…”
Section: Atherosclerosismentioning
confidence: 99%
“…Vitamin D deficiency is affecting more than one billion people to approximately 50% of population worldwide [762][763][764] . Shortage of vitamin D induced atherosclerosis and high blood pressure in mice [765] .…”
Section: Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation